Identifying sources of resistance to change in healthcare. (28th January 2008) - Landaeta, Rafael E.; Mun, Ji Hyon; Rabadi, Ghaith; Levin, David
The continuous introduction of new healthcare technologies, as well as the proliferation of new processes that guarantee better treatment and care of patients, suggests that the pace of the healthcare environment has been accelerating in recent years. Therefore, it is very important to identify and address sources of resistance to change before, during, and after change efforts are made in healthcare. This research applied a phenomenology approach to evaluate 24 known sources of resistance to change in a change effort at a section of Sentara Leigh Hospital in Norfolk, Virginia. The results of this investigation suggest that there are sources of resistance to change that are specific only to the healthcare sector. This finding is important because it provides a foundation that can be used to extend our understanding of both healthcare organisations and sources of resistance to change.